Fatores influentes da satisfação no trabalho de servidores públicos da Universidade Federal de São Carlos - Luchini, Thiago Corrêa (2016)
The main objective of this study was to highlight and analyze the factors present in the work environment that influence the satisfaction of the technical-administrative employees of the Federal University of São Carlos, who work in Academic Departments. The theoretical framework adopted was Locke's Theory of Work Satisfaction, along with the interaction of other psychosocial aspects related to work, such as Motivation; Sense, Health and Ability to Work; Personal Identity; Organizational Identity; And the question of Leadership. Through the application of questionnaires, among them, the Satisfaction Questionnaire at Work S20 / 23 - adapted to the Brazilian reality, a descriptive and exploratory research was carried out. An analytical survey and logistic regression were used to analyze the data. The survey had a very significant sample, covering 124 individuals out of a total of 147 possible, considerably increasing the reliability of the data obtained, mainly in relation to the data found in Questionnaire S20 / 23, with significantly higher Cronbach's alpha indices. Once verified the degree of satisfaction of the researched agents, it was possible to evidence some factors that may be affecting the organizational behavior of the subjects studied in a way that leads them to the dissatisfaction and that can not be neglected by the organization. In this sense, this work contributed to a better analysis and understanding of job satisfaction within the public organizational context, pointing to ways of creating and consolidating in the individual a sense of belonging that does not come substantially through extrinsic rewards, but mainly through Rewards, where leadership has a primordial role that, together with the institutional mission, are fundamental for the good progress of the organizational flows of the University and of organizations in general.